Allocation and productivity of time in new ventures of female and male entrepreneurs - Ingrid Verheul; Martin A. Carree; A. Roy Thurik (Max Planck Institute of Economics, 2006)
This paper investigates time allocation decisions in new ventures of female and male entrepreneurs using a new model that distinguishes between effects of preferences (what they like) and productivity (what they are good at) on the number of working hours. Using data of 1203 entrepreneurs we find that the preference for work time in new ventures is related to the motivation for starting up a business, the propensity to take risk and the availability of other income. Productivity of work time is explained by human, financial and social capital and outsourcing. This study also evaluates actual profit effects one year after start-up. With respect to gender we find that on average women invest less time in the business than men. This can be attributed to a lower productivity per hour worked, due to lower endowments of human, social and financial capital.
More recent version: http://hdl.handle.net/10419/110998
Keywords: J22; L26; M13; 330; time allocation; preferences; productivity; gender; new ventures; Unternehmer; Weibliche Führungskräfte; Zeitallokation; Unternehmensgründung